La Falsa Atribución de Paternidad por parte de la Madre, su Tipificación y Penalización - Correa Jiménez, Marianela Alexandra (2019)
The present work of legal research titled ''THE FALSE ATTRIBUTION OF PATERNITY BY THE MOTHER, ITS TYPING AND PENALIZATION '' demonstrates its importance in view of the fact that it seeks to protect the rights of the family members, the people affected by the false attribution of paternity as are the father to whom it is attributed and the son; thus, it is also sought to limit these acts through the imposition of a penal sanction. For this we must start with the understanding that the family is recognized as the superstructure that forges society. The first organization and the most primitive that has existed in the times. Its importance is essential from the social point of view because the members of the family are in charge of cementing values and principles to the new members so that they can become part of society. In the family structure we find important figures such as fatherhood, motherhood, filiation, identity, which revolve around the individual and therefore are transcendental in their formation and development. The links between the members of the family are essential in the development of the person, the filiation is the biological or legal nexus that allows to establish a parental relationship between parents and children, as well as to emerge intimate or emotional bonds that are strengthened by coexistence mutual However, what happens when verifying by means of an act of impugnation of paternity, the absence of biological links between the father and son, when these believed to have consanguinity relations? The affective bonds that 5 arose between these two members of the family nucleus are destabilized and the subsequent consequences may be triggered by material and subjective damage, as well as violation of rights in the victims of the deception produced by the mother. In the development of this research, the literature review is structured by the conceptual framework, the doctrinal framework, the normative framework and comparative law. Continuing with their development, they describe the methods applied, the materials used, the techniques used, including surveys and interviews, which allowed gathering information for the sustenance of the investigation on the false attribution of paternity made by the mother. With this information will be proven the damage caused by the false attribution of paternity and the need to regulate these acts. Below are the results, conclusions and recommendations of the same research that were collected after the analysis that was made of the results of the surveys, case studies and comparative legislation.